(3TQM GdMGhjs - (3CHh YHO Gddg eMeO (B( (3Hf SHW GdbRhjfi (B)s; (3GdeGhQOj , CHh GdMSf,J (B450 (3g` s ((3eMeO Hf YKeGf Hf LHQjd s)
(3ChdgG (B:s
(3GdMeO ddg GdeYR ddYde hHYO adeG cGf ef GdCeQ GdhGVM Cf GdabgGA GdReGf aVd EgJeGe HeOGQSI GdcJGH GdehShe HGdMGhi GdefShH Edi LOi aCLHJg Edi Pdc , hSejJg HGdcGP(B" s
(3BNQgG (B:s
(3hhba GdhdGA (B: (3Ci hdGA GdeSJhdOI Hjf YUHJi GdTQjcjf dYOe GdJQLjM hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3cJH eJf GdMGhi HGdMeQIs
(3Ydi GdfSNI JbjjOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs